When the smoke clears: expertise, learning and policy diffusion. (3rd June 2014) - Shipan, Charles R.; Volden, Craig
Abstract: In federal systems, governments have the opportunity to learn from the policy experiments – and the potential successes – of other governments. Whether they seize such opportunities, however, may depend on the expertise or past experiences of policymakers. Based on an analysis of state-level adoptions of antismoking restrictions targeted towards youths, we find that US states are more likely to emulate other states that have demonstrated the ability to successfully limit youth smoking. In addition, we find that political expertise (as captured by legislative professionalism) and policy expertise (as captured by previous youth access policy experiments at the local level) enhance the likelihood of emulating policy successes found in other states. As such, we establish that internal expertise and external learning are complements, rather than substitutes.